Pengaruh Pertumbuhan Perusahaan dan Likuiditas terhadap Kebijakan Dividen pada Perusahaan yang Terdaftar dalam Indeks High Dividend 20 (Jurnal Simki Economic, 2025)
The purpose of this study is to examine how dividend policy for businesses listed on the Indonesia Stock Exchange High Dividend Index 20 is affected by company growth and liquidity between 2018 and 2023. This study uses the dividend payout ratio to measure dividend policy, asset growth to measure company growth, and current ratio to analyze liquidity. This study uses a quantitative methodology with panel data regression. The sample includes 192 research data points from 32 purposefully selected organizations. The findings indicate that companies with rapid growth prefer to retain earnings to finance expansion, and this has a negative and significant impact on dividend policy. However, liquidity has a beneficial and significant impact on dividend policy, indicating that businesses with high levels of liquidity are more prepared to pay dividends regularly. The findings of the study indicate that dividend policy is significantly affected by company growth and liquidity.